Attributes of Woodland Caribou Migration Habitat in West-Central British Columbia - Lance, Art N.; Mills, Barry (Rangifer, 1996)
We examined sites used by 73 caribou located by radio-tracking during spring migration through a forested travel corridor. The physical and botanical characteristics of these sites were described to find what features (if any) distinguished them from the forest at large. Raised and open aspect, sparse tree cover, free-draining soils, and a simple flora with abundant lichens were features common to all the sites, but were lacking in the denser forest around. Scores for these attributes were ordinated by multidimensional scaling of similarities and differences from site to site. Separate searings for (i) terrain features, (ii) tree cover attributes, and (iii) floristic content each yielded a single cluster of points with few outliers and no particular pattern or trend. The inference is that the sites conformed to a single type with limited variation. A profile of the distinguishing characteristics was compiled and then applied to transects through the general migration area by persons unfamiliar with it beforehand. Sites which matched the profile proved easy to identify, even though they comprised only a small proportion of the area. Sites with high scores for the most distinctive attributes had more caribou at the time of radio-tracking.